2021
DOI: 10.4149/bll_2021_129
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of D-dimer in hospitalized COVID-19 patients

Abstract: INTRODUCTION: In COVID-19 patients, the determination of the relationship between elevated D-dimer level and prognosis and the determination of thrombosis formation in the early stages of the disease are very important. The aim of this study was to investigate the prognostic role of D-dimer levels based on presentation in patients hospitalized with the diagnosis of COVID-19. METHOD: The study was conducted on patients hospitalized with the diagnosis of laboratory-confi rmed COVID-19 between March 11 and April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Among the maternal outcomes, we found an extremely high case fatality ratio (26.2%) compared with similar studies [ 16 , 36 ], associated with the presence of poor prognosis markers such as elevated lactate dehydrogenase, C-reactive protein, ferritin, and D dimer, as well as thrombocytopenia and lymphopenia [ 30 , 37 49 ]. An increased risk of abortions and stillbirth in patients with COVID-19 has been described in larger studies [ 17 , 50 , 51 ], a pattern observed in our study with a higher proportion within the dead pregnant women, similar to that described in a Latin-American study [ 21 ], with the exception of the proportion of stillbirth.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Among the maternal outcomes, we found an extremely high case fatality ratio (26.2%) compared with similar studies [ 16 , 36 ], associated with the presence of poor prognosis markers such as elevated lactate dehydrogenase, C-reactive protein, ferritin, and D dimer, as well as thrombocytopenia and lymphopenia [ 30 , 37 49 ]. An increased risk of abortions and stillbirth in patients with COVID-19 has been described in larger studies [ 17 , 50 , 51 ], a pattern observed in our study with a higher proportion within the dead pregnant women, similar to that described in a Latin-American study [ 21 ], with the exception of the proportion of stillbirth.…”
Section: Discussionsupporting
confidence: 47%
“…However, it is impossible to conclude because it is necessary to consider unassessed variables such as dose, disease severity, and even the timing of the pandemic, as the role and indication of antithrombotics in managing COVID-19 were unknown at the beginning of the pandemic. Among the maternal outcomes, we found an extremely high case fatality ratio (26.2%) compared with similar studies [16,36], associated with the presence of poor prognosis markers such as elevated lactate dehydrogenase, C-reactive protein, ferritin, and D dimer, as well as thrombocytopenia and lymphopenia [30,[37][38][39][40][41][42][43][44][45][46][47][48][49]. An increased risk of abortions and stillbirth in patients with COVID-19 has been described in larger studies [17,50,51], a pattern observed in our study with a higher proportion within the dead pregnant women, similar to that described in a Latin-American study [21], with the exception of the proportion of stillbirth.…”
Section: Discussionmentioning
confidence: 64%
“…In patients with mesenteric iscaemia, the reported postoperative mortality is 23.8%, especially during the first 30 days 14 . Elevated D-dimer level ≥0.5 is an independent risk factor for mortality in COVID-19 patients 16.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, in line with earlier research' findings, the current investigation revealed higher D-dimer levels in COVID-19 patients with extended PT and APTT. Previous studies are reported around 30% of the patients, who were primarily older patients with concomitant conditions and non survivors, had thrombocytopenia [ 12 - 13 ]. When compared to patients less than 60 years of age, patients over 60 years of age had longer PTs and higher INRs, and PTs longer than 27 seconds were also deadly in 42% of cases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%